A fully hydrophobic eutectic gel and its preparation method and application

By using high ionic conductivity and polymerizable hydrophobic imidazole salt eutectic solvents, the problem of existing eutectic gels being easily absorbed and deactivated in high humidity environments is solved, and high ionic conductivity and stability in high humidity environments are achieved, and suitable for strain sensors.

CN116375939BActive Publication Date: 2025-04-11ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310385657.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-04-11
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

The existing eutectic gels are prone to water absorption and inactivation in high humidity environments, and the hydrophobic eutectic solvent with quaternary ammonium salts as hydrogen bond receptors have low ionic conductivity, which cannot meet the application requirements of strain sensors.

Method used

A hydrophobic imidazole salt eutectic solvent with both high ionic conductivity and polymerization is prepared by mixing and heating with a hydrogen bond donor, adding a crosslinking agent and an initiator to form a prepolymerized liquid. After removing bubbles and heating, a fully hydrophobic eutectic gel is prepared.

Benefits of technology

The fully hydrophobic eutectic gel prepared has high ionic conductivity and stability in high humidity environments. It is suitable for strain sensors. The material is cheap, non-toxic and environmentally friendly. The preparation method is simple and practical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116375939B_ABST
    Figure CN116375939B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of strain sensor technology, and in particular to a fully hydrophobic eutectic gel and a preparation method and application thereof. The preparation method of the fully hydrophobic eutectic gel provided by the present invention comprises the following steps: preparing a hydrophobic eutectic solvent having both high ionic conductivity and polymerizability; after uniformly mixing a cross-linking agent, an initiator, and a hydrophobic eutectic solvent, a polymerization reaction is carried out to obtain the fully hydrophobic eutectic gel. The fully hydrophobic eutectic gel provided in the present application has a good humidity impedance effect in a high humidity environment, so that it has good ionic conductivity stability in different humidity environments. Therefore, the flexible strain sensor based on the fully hydrophobic eutectic gel has good sensing stability and practicality in different humidity environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of strain sensors, and in particular to a fully hydrophobic eutectic gel and a preparation method and application thereof. Background Art

[0002] Hydrogels have high ionic conductivity and adjustable mechanical properties, and are ideal candidate materials for electronic skin, wearable electronic devices, and soft robots. However, hydrogels have poor temperature resistance, especially dehydration and inactivation at high temperatures and solidification and freezing at low temperatures, which seriously affects the long-term effectiveness of hydrogels. Researchers have proposed using non-volatile ionic liquids to prepare ionic gels to solve the freezing and dehydration problems in hydrogels. However, ionic gels have the disadvantages of easy water absorption and inactivation, high price, and toxicity. At present, researchers have shifted their targets to eutectic gels with high conductivity and stability, easy preparation, and good biocompatibility. However, the eutectic solvents used in eutectic gels are mostly quaternary ammonium salt eutectic solvents, which also have the disadvantage of easy water absorption and inactivation. The ionic conductivity of hydrophobic eutectic solvents with quaternary ammonium salts as hydrogen bond acceptors (such as tetraheptyl ammonium chloride, tetrabutyl ammonium chloride, methyl trioctyl ammonium chloride, and choline chloride) is very low (usually less than 0.005S / m), which cannot meet the application requirements of strain sensors. Imidazolium salts generally have high ionic conductivity, but there is no report in the literature on the preparation of eutectic solvents using imidazolium salts as hydrogen bond acceptors.

[0003] Therefore, the preparation of fully hydrophobic eutectic gel-based strain sensors remains a very challenging task. Summary of the invention

[0004] The purpose of the present invention is to provide a fully hydrophobic eutectic gel and a preparation method and application thereof. The fully hydrophobic flexible strain sensor provided by the present invention can be used in a high humidity environment.

[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a fully hydrophobic eutectic gel, comprising the following steps:

[0007] (1) preparing a hydrophobic eutectic solvent having both high ionic conductivity and polymerizability;

[0008] (2) adding a crosslinking agent and an initiator respectively and dissolving them fully to prepare a prepolymer solution;

[0009] (3) The prepolymer liquid is degassed, then sealed in a mold, and heated to initiate polymerization, thereby obtaining the fully hydrophobic eutectic gel.

[0010] The preparation method of the hydrophobic eutectic solvent with high ionic conductivity and polymerizability described in the present invention is to mix an imidazole salt (hydrogen bond acceptor) containing a carbon-carbon double bond with a hydrophobic hydrogen bond donor, heat at 60° C. for 2 hours, and cool to room temperature to obtain a hydrophobic imidazole salt eutectic solvent.

[0011] Preferably, the hydrogen bond acceptor is one or more of 1-allyl-3-methylimidazole chloride, 1-allyl-3-methylimidazole bromide, 1-allyl-3-vinylimidazole chloride, 1-allyl-3-vinylimidazole bromide, 1-vinyl-3-butylimidazole chloride, 1-vinyl-3-butylimidazole bromide, 1-vinyl-3-ethylimidazole chloride and 1-vinyl-3-ethylimidazole bromide; more preferably 1-allyl-3-vinylimidazole chloride.

[0012] Preferably, the hydrogen bond donor is one or more of 4-chlorophenol, methylparaben, ethylparaben and p-cresol; more preferably p-cresol.

[0013] Preferably, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1 to 1:2.5.

[0014] Preferably, the cross-linking agent is polyethylene glycol dimethacrylate.

[0015] Preferably, the initiator is one or more of azobisisobutyronitrile, ammonium persulfate, and benzoyl peroxide; more preferably, benzoyl peroxide.

[0016] Preferably, the cross-linking agent accounts for 0.5 wt% of the mass of the hydrophobic eutectic solvent; and the initiator accounts for 0.5 wt% of the mass of the hydrophobic eutectic solvent.

[0017] Preferably, the heating temperature in step (3) is 80° C., and the heating time is 1 to 24 hours, more preferably 8 hours.

[0018] The present invention also provides the use of the fully hydrophobic eutectic gel described in the above technical solution in a strain sensor.

[0019] The present invention also provides a strain sensor, comprising the above-mentioned fully hydrophobic eutectic gel and nickel foam, wherein the fully hydrophobic eutectic gel is connected with the nickel foam.

[0020] The imidazole salt in the present invention gives the hydrophobic eutectic solvent high ionic conductivity; the carbon-carbon double bond structure gives the eutectic solvent polymerizability, and after copolymerization with a crosslinking agent, a eutectic gel with excellent mechanical properties can be prepared; the hydrophobic hydrogen bond donor gives the eutectic gel good hydrophobicity. The swelling rate of the fully hydrophobic eutectic gel in water is less than 2%, the contact angle of a water droplet on the surface of the fully hydrophobic eutectic gel is not less than 90°, and the ionic conductivity of the fully hydrophobic eutectic gel in air, 100% RH (relative humidity) and water is greater than 0.09S / m, and has stable ionic conductivity (after immersion in water for 10 days, the ionic conductivity is still greater than 0.09S / m).

[0021] Compared with the prior art, the beneficial effects of the present invention include:

[0022] (1) The hydrophobic imidazolium salt eutectic solvent provided by the present invention has both high ionic conductivity and polymerizability, which can effectively improve the hydrophobicity and conductivity of the eutectic gel, thereby making the eutectic gel have good humidity impedance effect in a high humidity environment.

[0023] (2) The eutectic gel prepared by the preparation method of the present invention has good ionic conductivity stability in a high humidity environment. Therefore, the fully hydrophobic eutectic gel-based strain sensor of the present invention has good sensing stability and practicality in a high humidity environment.

[0024] (3) The materials of the present invention are inexpensive, non-toxic, environmentally friendly, and abundant and readily available.

[0025] (4) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The ionic conductivity of the fully hydrophobic eutectic gel obtained in Examples 1-4 in air, 100% RH (relative humidity) and water.

[0027] Figure 2 is the contact angle of a water drop on the surface of the fully hydrophobic eutectic gel obtained in Examples 1-4.

[0028] Figure 3 The tensile curves of the fully hydrophobic eutectic gels obtained in Examples 1-4 in air, 100% RH (relative humidity) and water are shown (A is Example 1; B is Example 2; C is Example 3; D is Example 4).

[0029] Figure 4 Graph showing the stretching-sensing performance of the strain sensor obtained in Example 5 in air, 100% RH and water. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0031] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0032] Example 1

[0033] The preparation method of the fully hydrophobic eutectic gel in this embodiment is as follows:

[0034] (1) Preparation of a hydrophobic eutectic solvent having high ionic conductivity and polymerizability: A hydrogen bond acceptor (1-allyl-3-vinyl imidazolium chloride) and a hydrogen bond donor (p-cresol) were mixed according to the ingredient ratio shown in Table 1, heated at 60° C. for 2 h, and cooled to room temperature to obtain a hydrophobic eutectic solvent.

[0035] (2) According to the ingredient list ratio shown in Table 1, a crosslinking agent and an initiator are added respectively to prepare a prepolymer solution, wherein the crosslinking agent is polyethylene glycol dimethacrylate and the initiator is benzoyl peroxide.

[0036] (3) using ultrasound to remove bubbles from the mixed solution, and then sealing the mixed solution in a light-transmitting mold and heating it at 80° C. for 8 h to obtain the fully hydrophobic eutectic gel.

[0037] Embodiment 2-4

[0038] The difference between Example 2-4 and Example 1 is that the raw material formula ratio of the fully hydrophobic eutectic gel is different, please refer to Table 1 for details, and the rest of the processes are exactly the same.

[0039] Comparative Example 1

[0040] After mixing 20 g of choline chloride (hydrogen bond acceptor) and 20 g of p-cresol (hydrogen bond donor), the mixture was heated at 60° C. for 2 h and cooled to room temperature to obtain a quaternary ammonium salt hydrophobic eutectic solvent. Since choline chloride has no polymerizable functional groups, a eutectic gel cannot be formed after adding a crosslinker and an initiator, and therefore the ionic conductivity is only compared with that of the imidazole salt hydrophobic eutectic solvent in Example 1.

[0041] Comparative Example 2

[0042] 20 g of tetrabutylammonium chloride (hydrogen bond acceptor) and 20 g of p-cresol (hydrogen bond donor) were mixed, heated at 60° C. for 2 h, and cooled to room temperature to obtain a quaternary ammonium salt hydrophobic eutectic solvent. Since tetrabutylammonium chloride has no polymerizable functional group, it cannot form a eutectic gel after adding a crosslinker and an initiator, so the ionic conductivity is only compared with that of the imidazole salt hydrophobic eutectic solvent in Example 1.

[0043] Comparative Example 3

[0044] After mixing 20 g of trioctylammonium chloride (hydrogen bond acceptor) and 20 g of ethylparaben (hydrogen bond donor), the mixture was heated at 60° C. for 2 h and cooled to room temperature to obtain a quaternary ammonium salt hydrophobic eutectic solvent. Since trioctylammonium chloride has no polymerizable functional groups, a eutectic gel cannot be formed after adding a crosslinker and an initiator, and therefore the ionic conductivity is only compared with that of the imidazole salt hydrophobic eutectic solvent in Example 1.

[0045] Comparative Examples 4-7

[0046] The difference between Comparative Examples 4-7 and Example 1 is that the ratio of the hydrogen bond acceptor (1-allyl-3-vinylimidazolium chloride) to the hydrogen bond donor (p-cresol) is different, as shown in Table 1 for details.

[0047] Table 1 Raw material formula of fully hydrophobic eutectic gel

[0048]

[0049] The hydrophobic eutectic gels prepared in Examples 1-4 were subjected to performance tests. The performance tests included the following aspects:

[0050] Ionic conductivity test: The eutectic gel was cut into three rectangular strips with a length of 1 cm, a width of 1 cm, and a thickness of 0.1 cm, and then placed in air, 100% RH, and water, respectively. After 24 hours, the resistance R of the eutectic gel was measured using an electrochemical workstation (CHI660E). Each sample was tested three times. The ionic conductivity σ (S / m) of the eutectic gel was calculated according to the following formula:

[0051] σ=0.01 / R

[0052] Swelling performance test: Put the eutectic gel with a mass of W0 into 25℃ deionized water, take it out after 24 hours and wipe it dry, weigh it and record it as W1, repeat the test three times for each sample and take the average value. The swelling rate SR of the eutectic gel is calculated according to the following formula:

[0053] SR=(W1-W0) / W0

[0054] Contact angle test: The eutectic gel was cut into rectangular strips with a length of 1 cm, a width of 1 cm, and a thickness of 0.1 cm. The contact angle of a water drop on the surface of the eutectic gel was tested using a JC2000C1 sessile drop contact angle meter.

[0055] Elongation at break test: Three eutectic gel samples were prepared for each example, and then placed in air, 100% RH, and water, respectively. After 24 hours, the elongation at break of each sample was tested using the method of GB3923-83Q.

[0056] Fracture strength test: Three eutectic gel samples were prepared for each example, and then placed in air, 100% RH, and water, respectively. After 24 hours, the fracture strength of each sample was tested using the method of GB3923-83Q.

[0057] Table 2 Ionic conductivity of eutectic solvents with different hydrophobicity

[0058] Example 1 Hydrophobic eutectic solvent obtained Comparative Example 1 Comparative Example 2 Comparative Example 3 Ionic conductivity (S / m) 0.114 0.003 0.003 0.002

[0059] It can be seen from Table 2 that the ionic conductivity of the imidazole hydrophobic eutectic solvent prepared by the present invention is significantly better than that of the quaternary ammonium salt eutectic solvent, and this method has not been reported.

[0060] Table 3 Performance data of fully hydrophobic eutectic gels of Examples 1 to 4

[0061]

[0062]

[0063] It can be seen from Table 3 that the fully hydrophobic eutectic gels prepared in Examples 1 to 4 have high ionic conductivity, low swelling rate and good hydrophobicity under different humidity conditions.

[0064] The fully hydrophobic eutectic gels prepared in Examples 1 to 4 were subjected to a tensile test. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that when the eutectic gels of Examples 1 to 4 are placed in air, 100% RH, and water, respectively, the elongation at break and the fracture strength of the fully hydrophobic eutectic gels do not change significantly, further indicating that the eutectic gels have good hydrophobicity. Among them, the eutectic gel of Example 1 has the largest elongation at break and fracture strength.

[0065] Table 4 Performance data of fully hydrophobic eutectic gel of Example 1 and Comparative Examples 5 to 7

[0066] Gel properties Example 1 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Ionic conductivity (S / m) 0.093 0.054 0.024 0.015 0.007 Elongation at break (%) 1617 702 632 585 795 Breaking strength(MPa) 0.018 0.012 0.011 0.013 0.014 Swelling rate (%) 1.4 1.3 1.1 1.0 1.1 Contact angle (ο) 101 94 92 95 94

[0067] It can be seen from Table 4 that, compared with Example 1, the ionic conductivity, elongation at break and breaking strength of the fully hydrophobic eutectic gels prepared in Comparative Examples 4 to 7 are significantly reduced, which may be caused by the reduction in the concentration of the imidazole salt.

[0068] Example 5

[0069] The fully hydrophobic eutectic gel described in Example 1 was cut into three strips with a length of 3 cm, a width of 1 cm, and a thickness of 0.2 cm. The strips were then placed in air, 100% RH, and water, respectively. After 24 hours, the cut fully hydrophobic eutectic gel was used as a sensing material and connected to the upper and lower surfaces of the eutectic gel using nickel foam to obtain a strain sensor.

[0070] The flexible strain sensor prepared in Example 5 was tested for stretch-sensing performance by an electrochemical workstation (CHI660). Specific method: 3 sensors were prepared in each example, and then placed in air, 100% RH, and water, respectively. The sensors were connected in series to the electrochemical workstation using wires, and the resistance change rate of the sensor under 100% strain was recorded. The results are shown in Figure 2. Figure 4 As shown in the figure, it can be seen that in air, 100% RH and water, the strain sensor has a stable and regular response signal, and the magnitude of the resistance change rate is basically the same, indicating that the fully hydrophobic eutectic gel in the strain sensor described in Example 5 has excellent stability, good sensing performance and environmental adaptability, and can present a stable response force-electric sensing signal even in a high humidity (100% RH and water) environment.

[0071] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a fully hydrophobic eutectic gel, characterized in that: The following steps are involved: (1) Preparation of hydrophobic eutectic solvents with high ionic conductivity and polymerizability; (2) adding a crosslinking agent and an initiator to a hydrophobic eutectic solvent to fully dissolve them to prepare a prepolymer solution; (3) removing bubbles from the prepolymer solution, then sealing it in a mold, and heating to initiate polymerization, thereby obtaining the fully hydrophobic eutectic gel; In step (1), the preparation method of the hydrophobic eutectic solvent having high ionic conductivity and polymerizability is as follows: after mixing the hydrogen bond acceptor and the hydrogen bond donor, heating at 60° C. for 2 h, and cooling to room temperature, the hydrophobic eutectic solvent is obtained; The hydrogen bond acceptor is one or more of 1-allyl-3-methyl imidazolium chloride, 1-allyl-3-methyl imidazolium bromide, 1-allyl-3-vinylimidazolium chloride, 1-allyl-3-vinylimidazolium bromide, 1-vinyl-3-butyl imidazolium chloride, 1-vinyl-3-butyl imidazolium bromide, 1-vinyl-3-ethyl imidazolium chloride and 1-vinyl-3-ethyl imidazolium bromide; The hydrogen bond donor is one or more of 4-chlorophenol, methylparaben, ethylparaben and p-cresol.

2. The method for preparing the fully hydrophobic eutectic gel according to claim 1, characterized in that: The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1 to 1:2.

5.

3. The method for preparing the fully hydrophobic eutectic gel according to claim 1, characterized in that: In step (2), the cross-linking agent is polyethylene glycol dimethacrylate; the initiator is one or more of azobisisobutyronitrile, ammonium persulfate, and benzoyl peroxide.

4. The method for preparing the fully hydrophobic eutectic gel according to claim 1, characterized in that: In step (2), the ratio of the cross-linking agent to the hydrophobic eutectic solvent is 0.5 wt %; the ratio of the initiator to the hydrophobic eutectic solvent is 0.5 wt %.

5. The method for preparing the fully hydrophobic eutectic gel according to claim 1, characterized in that: In step (3), the heating temperature is 80°C and the heating time is 1 to 24 h.

6. A fully hydrophobic eutectic gel, prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The swelling rate of the fully hydrophobic eutectic gel in water is less than 2%, the contact angle of a water droplet on the surface of the fully hydrophobic eutectic gel is not less than 90°, and the ionic conductivity of the fully hydrophobic eutectic gel in air, 100% RH and water is greater than 0.09 S / m.

7. Application of the fully hydrophobic eutectic gel according to claim 6 in the field of strain sensors.

8. A strain sensor, characterized in that: The method comprises the fully hydrophobic eutectic gel as described in claim 6 and nickel foam, wherein the fully hydrophobic eutectic gel is connected with the nickel foam.

Citation Information

Patent Citations

  • Imidazole polyion liquid gel electrolyte and preparation method thereof

    CN112185712A